Synthesis, characterisation and structural studies of amidinate and guanidinate alkaline earth–transition metal bonded complexes. (25th September 2016) - Green, Ross; Walker, Alicia C.; Blake, Matthew P.; Mountford, Philip
Graphical abstract: The first amidinate and guanidinate magnesium complexes with bonds to transition metals have been synthesised and structurally authenticated. IR and diffusion NMR spectroscopy provide further evidence for their structural forms in the solid state and solution. Abstract: Reaction of magnesium amidinate complexes of the form [MesC(NR)2 MgBr(OEt2 )]2 (R = i Pr, Dipp, Mes) with the potassium salts of transition metal anions K[CpFe(CO)2 ] (K[Fp]) and K[Co(CO)3 (PCy3 )](THF)2 gave the complexes MesC(NR)2 MgFp(THF) and MesC(NR)2 MgCo(CO)3 (PCy3 )(THF). Single crystal X-ray diffraction studies of MesC(NR)2 MgCo(CO)3 (PCy3 )(THF) for R = i Pr and Dipp confirm these to have Mg–Co bonds in the solid state. Reaction of the structurally similar magnesium guanidinate complex Me2 NC(NDipp)2 MgI(OEt2 ) with the aforementioned transition metal anions or K[Co(CO)3 (PPh3 )](THF) gave the series of complexes [Me2 NC(NDipp)2 MgFp]2, Me2 NC(NDipp)2 MgCo(CO)3 (PCy3 )(OEt2 ) and Me2 NC(NDipp)2 MgCo(CO)3 (PPh3 )(OEt2 ). Structural authentication by X-ray crystallography showed [Me2 NC(NDipp)2 MgFp]2 to be a very rare example of a base-free alkaline earth–transition bonded complex, having two Mg–Fe bonds. IR and diffusion NMR spectroscopy was carried out to gain further insight into the solid state and solution phase structures.